Partnerships: The effective harnessing of research for the advancement of animal agriculture in developing countries - Walsh, J. (Food and Agriculture Organization of the United Nations, 1993)
This paper summarises how an international research centre may hope to be effective by forging partnership arrangements with national research systems and with research institutions in industrialised countries. A major requirement for an effective partnership is that it is an integral part of the coordinating centre's operational strategies, with the potential partners being closely involved in the Development of the strategies. Also, the stakeholders in the partnership should be systematically consulted to check that the strategic choices made during programme formulation continue to be appropriate with regard to the changing priorities and values of the partners. The focus in the second part of the paper is on the collaborative research networks with which ILCA is associated; networks being the major means by which the centre forges relationships between and with rational programmes in livestock research in sub-Saharan Africa. The functions fulfilled by the networks are highlighted. The experience gained by ILCA in allying itself with national agricultural research systems and international partners in two areas of research - trypanosomiasis control and vertisols managment - is outlined to demonstrate the mode of operation of some networks. In the final section of the paper, the institutional support services required to service the operation of research partnerships are described.